2020
DOI: 10.3390/ijms21103442
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Biomaterials for Dental Tissue Regeneration

Abstract: Injectable biomaterials scaffolds play a pivotal role for dental tissue regeneration, as such materials are highly applicable in the dental field, particularly when compared to pre-formed scaffolds. The defects in the maxilla-oral area are normally small, confined and sometimes hard to access. This narrative review describes different types of biomaterials for dental tissue regeneration, and also discusses the potential use of nanofibers for dental tissues. Various studies suggest that tissue engineering appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 220 publications
(278 reference statements)
1
51
0
1
Order By: Relevance
“…Chemical and bioactive traits of HA, such as the ability to bind water molecules or forming a framework for cell migration, provide a convenient environment for the seeded cells, while its conductive function facilitates ingrowth of the surrounding tissues [ 25 , 29 ]. The application of HA is broad, including bone, cartilage, skin, eye, periodontal, or dental pulp tissue engineering [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical and bioactive traits of HA, such as the ability to bind water molecules or forming a framework for cell migration, provide a convenient environment for the seeded cells, while its conductive function facilitates ingrowth of the surrounding tissues [ 25 , 29 ]. The application of HA is broad, including bone, cartilage, skin, eye, periodontal, or dental pulp tissue engineering [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several scaffolds were investigated during the last two decades. Nowadays, the most studied scaffolds for periodontal application are hydrogels, films, fibers and 3D-printed scaffolds, realized using both synthetic and natural polymers ( Figure 1 ) [ 54 , 55 , 56 ].…”
Section: Main Scaffolds In Periodontal Tissue Regenerationmentioning
confidence: 99%
“…Sequentially, fibers have been deliberated for use in endodontic treatments/investigations. Haugen et al claim that nanofibers can be considered for pulp tissue engineering and regenerative endodontics due to their potential use for dental tissues [ 56 ]. Related studies have reported that fibers can act biomimetically to create microenvironments and behave as an appropriate scaffold for the pulp-dentine complex, mimicking the native pulp and function [ 57 ].…”
Section: Local Drug Delivery Systemsmentioning
confidence: 99%